MINERAL POTENTIAL MAPPING USING GEOGRAPHIC INFORMATION SYSTEMS (GIS) FOR GOLD MINERALIZATION IN WEST JAVA, INDONESIA - Seang Sirisokha; Lucas Donny Setijadji; I Wayan Warmada (Geological Engineering Department Universitas Gadjah Mada, 2015)
Western Java is a part of the Sunda Banda magmatic belt. This belt is well known to be host for several gold deposits in Indonesia, the distribution of 107 Au occurrences in this area was examined in terms of spatial association with various geological phenomena. The goal of this project is to use GIS to conduct weights of evidence (WofE) model for gold mineralization in West Java, Indonesia. A Geographic Information System (GIS) is a computer system for capturing, storing, querying, analyzing, and displaying geospatial data and weight of evidence method is one of the most important datadriven methods for mapping in GIS. The method is a probability based on technique for mapping mineral potential using the spatial distribution of known mineral occurrences. Therefore this method is very useful for gold potential mapping. There are six evidences maps such as NE–SW lineaments NW–SE Lineament, host rocks, heat sources, clay alteration and limonitic alteration, have been combined using a weights of evidence model to predict gold potential in West Java. The best predictive map generated by this method deﬁnes 21.62% (9902 km) of study area as favourable zones for gold mineralization further exploration work. It predicts correctly 74 (92.5%) of the 80 model deposits and predicts correctly 26 (96.35%) of the 27 validation deposits, has 6 main 2 prospective target for future exploration are located in Bayah Dome, southern mountain, Honjie Igneous Complex and Bogor zone, Purwakarta. Bayah Dome is highest potential area for gold deposit like Gunung Pongor, Cikidang, Cirotan, Ciawitali, Cikotok destricts and other deposits. The potential area of Au occurrences in research area is associated with NE–SW and NW–SE structure/ lineaments, dominated surrounding the Tertiary intrusive rock unit and hosted in Miocene to Pleistocene lithology rock unit.